Turning solid waste incineration ashes into a usable material in construction - Chatila, Jean G. (2003)
This paper describes a largely experimental investigation for turning solid waste incineration ashes into a usable material in concrete construction. The result is a method for incineration ashes to be disposed of in an environmentally safe method without creating a nuisance. In addition, there is a possibility to increase the compressive strength of concrete, reduce landfill volumes, and protect the public from environmental and health impacts of poor waste management. Based on the current applications and proportions, the flexural strength of concrete was affected. The variation of strength ranged between an increase of 12% and a decrease of 50% depending on the proportions, gradation, and source of ashes added. Furthermore, the dissolution of these ashes in water and acetic acid was checked and did not pose a problem within the applicable standards.